A new microfluidic model to study dendritic remodeling and mitochondrial dynamics during axonal regeneration of adult zebrafish retinal neurons - Van Dyck, Annelies; Masin, Luca; Bergmans, Steven; Schevenels, Giel; Beckers, An; Vanhollebeke, Benoit; Moons, Lieve (Frontiers in Molecular Neuroscience, 2023)
Unlike mammals, adult zebrafish are able to fully regenerate axons and functionally recover from neuronal damage in the mature central nervous system (CNS). Decades of research have tried to identify the mechanisms behind their spontaneous regenerative capacity, but the exact underlying pathways and molecular drivers remain to be fully elucidated. By studying optic nerve injury-induced axonal regrowth of adult zebrafish retinal ganglion cells (RGCs), we previously reported transient dendritic shrinkage and changes in the distribution and morphology of mitochondria in the different neuronal compartments throughout the regenerative process. These data suggest that dendrite remodeling and temporary changes in mitochondrial dynamics contribute to effective axonal and dendritic repair upon optic nerve injury. To further elucidate these interactions, we here present a novel adult zebrafish microfluidic model in which we can demonstrate compartment-specific alterations in resource allocation in real-time at single neuron level. First, we developed a pioneering method that enables to isolate and culture adult zebrafish retinal neurons in a microfluidic setup. Notably, with this protocol, we report on a long-term adult primary neuronal culture with a high number of surviving and spontaneously outgrowing mature neurons, which was thus far only very limitedly described in literature. By performing time-lapse live cell imaging and kymographic analyses in this setup, we can explore changes in dendritic remodeling and mitochondrial motility during spontaneous axonal regeneration. This innovative model system will enable to discover how redirecting intraneuronal energy resources supports successful regeneration in the adult zebrafish CNS, and might facilitate the discovery of new therapeutic targets to promote neuronal repair in humans.